Communality and Discord in an Early Neolithic Settlement Agglomeration: The LBK Site of Vráble, Southwest Slovakia. Issue 3 (August 2020) - Furholt, Martin; Müller-Scheeßel, Nils; Wunderlich, Maria; Cheben, Ivan; Müller, Johannes
Abstract : Our research at the large LBK settlement site of Vráble, southwest Slovakia, revealed dynamics of social integration and antagonisms unfolding in an agglomerated, early farming community. During its lifespan from 5250 to 4950 bc, it constantly grew until around 5050 bc it was inhabited by about 70 contemporaneous longhouses. We found that Vráble consisted of markedly autonomous farmstead units that were held together by village-wide social institutions including sharing and communality. Nevertheless, from the beginning, a contradiction between particular farmstead and collective village and neighbourhood interests existed and rose. Towards the end of the village's existence, around 5075 bc an elaborate enclosure was constructed around one of the three neigbourhoods, actively blocking contact with the others. Along this enclosure, human bodies were deposited, showing a social categorization that we interpret as relating to social inequality. This rising level of conflict and emerging social inequality was, we argue, not sustainable under the conditions of early farming societies and led to the village's abandonment at 4950 bc .